Hambatan dalam Menerapkan Perawatan yang Berpusat pada Keluarga di Lingkungan Pediatrik - Mufida, Mufida; Mardiah, Wiwi; Rachmawati, Windy (Journal of Telenursing (JOTING), 2023)
This study aims to explore barriers to family-centered care (FCC) in the pediatric care area. The method used is a systematic review with literature searches from several online databases. The results showed that parents' perceived knowledge regarding FCC, namely the primary nurse-caregiver relationship, ward structure/policies, knowledge, ethical issues, limited health service resources, limited time in providing services, the nature of chronic disease, medical paternalism and professional mindset influenced FCC implementation. In conclusion, these findings provide strong evidence for understanding what is most important to nurses and the barriers to family-centered care (FCC) in the pediatric care area. Keywords: Barriers, Family-centered care, Pediatric